Smart Design for Potentiometric Detection. Issue 3 (12th February 2015) - Shishkanova, Tatiana V.; Král, Vladimir; Fitl, Přemysl; Vrňata, Martin; Matějka, Pavel
Abstract This new design of potentiometric sensor involves 4‐mercaptophenylboronic acid (MPBA) evaporated onto a gold layer sputtered onto the surface of a plasticized poly(vinyl chloride) membrane based on a pH indicator. Fourier‐transform infrared spectroscopy confirms the presence of the pH indicator in close contact with the sputtered gold layer, and the covalent fixing of MPBA molecules onto this gold layer. The changes in pH resulting from the interaction between MBPA and the model saccharide (glucose) are reflected in the changes in the membrane capacitance and the potentiometric signal. The potentiometric sensor responds over the concentration range from 0.3 to 29.7 mM glucose.